A MULTICENTER STUDY TREATMENT ADHERENCE OF HYPERTENSION FOCUSED ON PRIMARY HEALTH CARE IN INDONESIA - Sulistiyowatiningsih, Endang; Herawati, Mutiara (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Hypertension today has a remained a focus in developing countries. This study aim was to determine the treatment adherence measured by the 8-item Morisky Medication Adherence Scale (MMAS-8) in hypertensive outpatients. Methods: A cross-sectional study was carried out with hypertensive patients older than 18 y, treated at eight of the primary health care in Special Region of Yogyakarta through interviews, between January and April 2016. Adherence was determine by MMAS-8 version translated for this study. Results: The patients consider low adherence (score<6), moderate adherence (score 6â€“7) and high adherence when they had a score equal to 8 at the MMAS-8. The prevalence of adherence among the 233 patients in primary healthcare showed the majority was lower adherence (57.90%), the moderate adherence (30.25%) and the high adherence (11.82%). The average adherence value acoording to the MMAS-8 was 5.2 (Â±1.7). Conclusion: Non-adherence treatments of hypertensive outpatients in primary healthcare was highest through application of MMAS-8Â